Epoxy/PCL nanocomposites: Effect of layered silicate on structure and behavior - J. Rotrekl; L. Matejka; L. Kapralkova; A. Zhigunov; J. Hromadkova; I. Kelnar (eXPRESS Polymer Letters)
The effect of clay-induced morphological transitions on the structure formed in the course of reactively induced phase separation (RIPS) and its impact on the properties of epoxy/polycaprolactone (PCL) nanocomposites were studied. The effect of organophilized montmorillonite on the behavior of epoxy containing 5–30% PCL was strongly dependent on the epoxy/PCL system composition. With a supercritical 20% PCL content, the increasing amounts of clay led to changes in the morphology that produced phase inversion, causing radical changes in the mechanical behavior. The main effect of the clay, which was located preferentially in the epoxy, was to influence the significant dynamic asymmetry (and thus the phase behavior). The simultaneous pinning effect of the clay on the phase separation changed the composition and parameters of the coexisting phases. The evaluation of the structure-properties relationship indicated the significant potential for nanoclays to control the behavior of thermoplastic- modified epoxy systems.